DIETARY LYSINE REQUIREMENT OF JAVA BARB (Puntius javanicus BLEEKER, 1855) FINGERLINGS TO OPTIMIZE FEED EFFICIENCY, GROWTH, AND NUTRIENT CONTENTS - Diana Rachmawati; Istiyanto Samidjan; Tita Elfitasari; Rosa Amalia; Dewi Nurhayati (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2021)
The slow growth of the Java barb (Puntius javanicus Bleeker, 1855) fingerlings is due to the feeding of plant-based protein which is usually lack of lysine.  The lack of it, can hinder the feed efficiency and growth. The best way to solve the problem is by adding lysine in the diet. The objectives of the study were to determine optimal needs of lysine to increase feed efficiency, growth, and nutrient contents of Java barb.  The fish samples were fingerlings of Java barb which weighed from 3.26 to 3.78 g-1 fish. The feed comprised 30% isoprotein and 262 Kcal isoenergy supplemented with lysine amino acid.  The dosages of the lysine in the diet were 1.25% (A1), 1.5% (A2), 1.75% (A3), 2.0% (A4), 2.25% (A5), and 2.5% (A6) of dried diets. The parameters observed were relative growth rate (RGR), apparent digestibility coefficients of protein (ADCp), efficiency of feed usage (EFU), feed conversion ratio (FCR), protein efficiency ratio (PER), survival rate (SR), hepatosomalic index (HSI), viscerosomatic index (VSI) and nutrient contents of Java barb. The results of the study disclosed that the enrichment of lysine into the diet increased the feed utilization, the growth and the nutrient contents of Java barb.  The needs of lysine for Java Barb (Puntius javanicus) fingerlings to optimize feed efficiency, growth, and nutrition contents ranged from 1.58% to-1.70% dried diet (5.3 to 5.6 % of protein diet).